Digital Competency Analysis and Financial Literacy as a Catalyst for Innovation and Student Business Growth in the 5.0 Era - Irma Ningsih; Iin Nurbudiyani; Muhammad Noor Fitriyanto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Background: The emergence of Society 5.0 presents both challenges and opportunities for university students, particularly in entrepreneurship. Aim: This study aimed to analyze digital competence and financial literacy as catalysts for innovation and business growth among student entrepreneurs in the digital era. Method: A mixed-methods approach with a sequential explanatory design was employed. Data were collected from 115 students engaged in entrepreneurial activities through questionnaires, interviews, and focus group discussions. Result and Discussions: The quantitative findings showed that most students had moderate to high digital competence, particularly in using social media, e-commerce platforms, and basic design tools. However, their ability to use advanced digital tools, including digital analytics, paid advertising, and cybersecurity, remained limited. In terms of financial literacy, students demonstrated awareness of basic financial practices, such as separating personal and business finances and recording transactions, yet many still lacked strategic financial planning skills, including budgeting, investment risk assessment, and long-term financial forecasting. Pearson correlation analysis revealed a significant positive relationship between digital competence and student business growth (r = 0.614; p < 0.01), as well as between financial literacy and student business growth (r = 0.587; p < 0.01). These results indicate that higher levels of digital competence and financial literacy are associated with stronger business growth, including increased revenue, market expansion, and product innovation. Conclusions: The qualitative findings supported the quantitative results by identifying several barriers, such as limited practical training, insufficient curriculum integration, and lack of mentoring. This study concludes that strengthening digital and financial competencies is essential for fostering sustainable student entrepreneurship in the Society 5.0 era. Therefore, universities are encouraged to integrate practical digital skills, financial literacy, and entrepreneurial mentoring into entrepreneurship programs to better prepare students for real-world business challenges.